PENCALONAN CALEG TERPIDANA DALAM PEMILU 2024: TINJAUAN HUKUM ADMINISTRATIF TERHADAP IMPLEMENTASI PASAL 11 PKPU NO. 10 TAHUN 2023 - Fikarsyah, Muhammad Thoriq; Subiyatno, Subiyatno (Tanjungpura Legal Review, 2025)
Abstract General elections are a fundamental element in the democratic system that functions as a means of implementing people's sovereignty. In Indonesia, the implementation of elections is regulated in various regulations, including General Election Commission Regulation No. 10 of 2023, which regulates the requirements for the candidacy of legislative members. One of the important provisions in this PKPU is the prohibition for legislative candidates who are serving criminal sentences to run for office. However, the implementation of this regulation often faces challenges, as seen in the case of AUR, a candidate for legislative member from Ketapang Regency who managed to pass the Permanent Candidate List stage despite his status as a convict. This study aims to analyze the implementation of Article 11 of PKPU No. 10 of 2023 in the process of nominating legislative members in Ketapang Regency in the 2024 Election. The AUR case reflects weaknesses in the administrative verification process carried out by the General Election Commission and political parties, which allow unqualified candidates to remain in the running as candidates. This study examines the factors that cause negligence in verification and its impact on the implementation of honest and fair elections. The results of the study show that the lack of accuracy in verifying candidate data and weak coordination between the KPU, political parties, and the community are the main causes of this negligence. These findings emphasize the importance of stricter law enforcement and supervision at every stage of the election to maintain the integrity of the democratic process in Indonesia. This study also recommends improving regulations and procedures to ensure that elections are carried out in accordance with the principles of direct, public, free, confidential, honest, and fair. Abstrak Pemilihan umum merupakan elemen fundamental dalam sistem demokrasi yang berfungsi sebagai sarana pelaksanaan kedaulatan rakyat. Di Indonesia, pelaksanaan Pemilu diatur dalam berbagai regulasi, termasuk Peraturan Komisi Pemilihan Umum No. 10 Tahun 2023, yang mengatur syarat pencalonan anggota legislatif. Salah satu ketentuan penting dalam PKPU ini adalah larangan bagi calon legislatif yang sedang menjalani hukuman pidana untuk mencalonkan diri. Namun, implementasi regulasi ini seringkali menghadapi tantangan, seperti yang terlihat pada kasus AUR, seorang calon anggota legislatif dari Kabupaten Ketapang yang berhasil lolos hingga tahap Daftar Calon Tetap meskipun berstatus sebagai terpidana.Penelitian ini bertujuan untuk menganalisis implementasi Pasal 11 PKPU No. 10 Tahun 2023 dalam proses pencalonan anggota legislatif di Kabupaten Ketapang pada Pemilu 2024. Kasus AUR mencerminkan kelemahan dalam proses verifikasi administratif yang dilakukan oleh Komisi Pemilihan Umum dan partai politik, yang memungkinkan calon tidak memenuhi syarat tetap maju sebagai kandidat. Penelitian ini mengkaji faktor-faktor yang menyebabkan kelalaian dalam verifikasi dan dampaknya terhadap pelaksanaan Pemilu yang jujur dan adil. Hasil penelitian menunjukkan bahwa kurangnya ketelitian dalam verifikasi data calon serta lemahnya koordinasi antara KPU, partai politik, dan masyarakat menjadi penyebab utama terjadinya kelalaian tersebut. Temuan ini menekankan pentingnya penegakan hukum dan pengawasan yang lebih ketat dalam setiap tahapan Pemilu untuk menjaga integritas proses demokrasi di Indonesia. Penelitian ini juga merekomendasikan perbaikan regulasi dan prosedur untuk memastikan Pemilu dilaksanakan sesuai dengan prinsip langsung, umum, bebas, rahasia, jujur, dan adil.